Complete mitochondrial genome of Devario kakhienensis (Cypriniformes: Danionidae: Danioninae): genome characterization and phylogenetic consideration. Issue 9 (2nd September 2022) - Song, Lin; Chen, Xiao Jiang; Zhang, Sai; Wang, Quan
Abstract: Complete mitochondrial genome and phylogenetic analysis of Devario kakhienensis, endemic minnow from southwest China, for the first time was presented. It was determined to be a 16, 777 bp long circular molecule and the genome organization was consistent with that of Danioninae species published previously. Based on PCGs, the maximum likelihood phylogenetic analysis supported the close genetic relationship between D. kakhienensis and Devario interruptus . These data would contribute toward the genetic resource enrichment, and provide a valuable framework for future research in completely resolving phylogenetic relationships with the family Danionidae.